Static Strength Analysis of Meat Grinder Frame - Abdul Rahman Agung Ramadhan; Eko Aprianto; Abdul Muchlis (International Journal of Science, Technology & Management, 2021)
Meat is one of the agricultural commodities needed to meet protein needs, because meat contains high quality protein, which is able to contribute complete essential amino acids. The purpose of this paper is to design, analyze the static strength of the frame based on theoretical calculations and simulations on solidwork 2018 software. This machine consists of a frame, reservoir, grinding shaft, transmission, and electric motor. The results of the design obtained a Meat Grinding Machine with Length: 610 mm, Width: 500 mm and Height: 750 mm. The material used is 2024-O Alloy with a modulus of elasticity of 72,400 N/mm2. The load force obtained is 576.32 N. And the value from the analysis is the displacement value of 0.174 mm and for theoretical calculations, the displacement value is 0.176 mm. So, the value of the percentage error is 1.176%. For the von Mises value of 68,970 MPa, and for calculations based on the theory, the von Mises value is 52,499 MPa. So, the value of the error percentage is 0.238%. And for the value of the safety factor obtained a value of 1,087, and for calculations based on the theory, the value of the safety factor is 1.428. So, the value of the error percentage is 0.313%.